2017
DOI: 10.1007/s10570-017-1290-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of cellulose-coated oil-in-water emulsions

Abstract: The behaviors of cellulose chains and cellulose mini-crystal in oil-in-water emulsions were studied by molecular dynamics simulations to investigate the coating states and the structural features of cellulose in these emulsions. In oil-in-water emulsion, dispersed cellulose chains gradually assemble during the progress of the simulation, eventually surrounding the octane droplet. In case of a cellulose mini-crystal, the cellulose chain at the corner of the crystal first contacts with the octane droplet through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 49 publications
3
28
0
Order By: Relevance
“…The use of atomic force microscopy allows direct measurement of cellobiohydrolase activity on crystalline cellulose, supporting the models that cellobiohydrolase adsorbs to the hydrophobic faces of cellulose . A previous study has shown that mixing of a cellulose solution in ionic liquid with water and oil yields a stable dispersion of cellulose‐coated oil droplets in water, a phenomenon that was also indicated by molecular dynamics simulations . Furthermore, an aqueous dispersion of regenerated cellulose hydrogel particles results in the same effect as emulsifying oil in water .…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The use of atomic force microscopy allows direct measurement of cellobiohydrolase activity on crystalline cellulose, supporting the models that cellobiohydrolase adsorbs to the hydrophobic faces of cellulose . A previous study has shown that mixing of a cellulose solution in ionic liquid with water and oil yields a stable dispersion of cellulose‐coated oil droplets in water, a phenomenon that was also indicated by molecular dynamics simulations . Furthermore, an aqueous dispersion of regenerated cellulose hydrogel particles results in the same effect as emulsifying oil in water .…”
Section: Introductionsupporting
confidence: 62%
“…33 A previous study has shown that mixing of a cellulose solution in ionic liquid with water and oil yields a stable dispersion of cellulose-coated oil droplets in water, 34 a phenomenon that was also indicated by molecular dynamics simulations. 35 Furthermore, an aqueous dispersion of regenerated cellulose hydrogel particles results in the same effect as emulsifying oil in water. 21 In such emulsions the amorphous cellulose shell on the surface of the oil droplets presents a huge external surface that is porous and of a thickness at least an order of magnitude smaller than the average size of the cellulose hydrogel particles.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the variation of the mechanical properties and solubility of the cellulose chain, models of 19 groups of single cellulose chains in the amorphous region with the polymerization degrees of 2,4,6,8,9,10,12,16,20,25,30,35,40,50,60,70,80,90, and 100 were constructed using COMPASS and PCFF force fields. The model density obtained by W. Chen [21] was about 1.385 g/cm 3 , while K. Mazeau and L. Heux [11] achieved a model with four different densities of 1.34-1.3927 g/cm 3 by modeling with the same method and standpoint, and proposed that the density of cellulose in the amorphous region is 1.28-1.44 g/cm 3 .…”
Section: Models Buildingmentioning
confidence: 99%
“…They reported a good agreement between their cellulose microfibrils configuration and NMR experiments. The studies of xyloglucan adsorption on cellulose microfibril surface [81] and of cellulose interface with oil-in-water emulsion [82] are other examples of cellulose microfibril molecular simulation using CHARMM force field.…”
Section: Charmmmentioning
confidence: 99%